2021
DOI: 10.1093/jimb/kuab079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofStreptomycessp. LS462 with high productivity of echinomycin, a potent antituberculosis and synergistic antifungal antibiotic

Abstract: A biologically active microbial strain, designated as LS462, was isolated from a soil sample collected from Yaoli Virgin Forest of Jiangxi Province, China. The strain was able to produce a high yield of echinomycin (172 mg/L) even under non-optimized culture conditions and proposed to serve as a promising source of echinomycin. In this study, echinomycin exhibited strong anti-Mycobacterium tuberculosis H37Rv activity and synergistic antifungal effect with a greatly reduced dosage of posaconazole on Candida alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Echinomycin bound to DNA has been shown to inhibit transcription in bacteria and chromatin condensation and DNA replication in eukaryotes, ultimately leading to cell cycle arrest (Fok & Waring, 1972; Krasinska & Fisher, 2009; May et al, 2004; Sato et al, 1967; Ward et al, 1965; Waring & Makoff, 1974). Quinomycins have been shown to possess antimicrobial, antiviral, and antitumor activities (Carter et al, 1954; Chen et al, 2021; Dolma et al, 2003; Sato et al, 1969; Yoshida et al, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Echinomycin bound to DNA has been shown to inhibit transcription in bacteria and chromatin condensation and DNA replication in eukaryotes, ultimately leading to cell cycle arrest (Fok & Waring, 1972; Krasinska & Fisher, 2009; May et al, 2004; Sato et al, 1967; Ward et al, 1965; Waring & Makoff, 1974). Quinomycins have been shown to possess antimicrobial, antiviral, and antitumor activities (Carter et al, 1954; Chen et al, 2021; Dolma et al, 2003; Sato et al, 1969; Yoshida et al, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microbial pigments are preferred over their chemical counterparts. Added advantages are microbial pigment's ease of production and processing supplemented with diversified biological activities, such as antimicrobial, anticancer, antioxidant, and antituberculosis (Chatragadda & Dufossé, 2021 ; Chen et al., 2021 ; Silva et al., 2021 ). Different bacterial pigments with potential bioactivities have been summarized elsewhere (Venil et al., 2020 ; Celedón and Díaz, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the Streptomyces strains that produced the anti-Candida derivatives came from the most diverse environments. These included 16 studies collecting strains from distinct soil sediment samples [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 11 studies obtaining strains from lakes, seas and oceans [59][60][61][62][63][64][65][66][67][68][69][70], and 5 studies isolating them from marine sponges. Additionally, one study derived strains from marine corals [71], while insects such as wasps, ants and cockroaches contributed isolates in five studies [72][73][74][75][76].…”
Section: Streptomyces-derived Compounds With Anti-candida Activity De...mentioning
confidence: 99%